Study on the pore structure characteristics of interbedded shale oil and formation mechanisms of high-quality shale oil reservoirs in the Chang 7 Member, Yanchang Formation, Ansai Oilfield - LIU Yuhang; QIANG Wei; DANG Xin; LIU Bo; WEN Zhigang; TIAN Weichao; FAN Yunpeng (Dizhi lixue xuebao, 2025)
Objective  As a key producing horizon of the Ansai Oilfield in the Ordos Basin , the pore structure of Chang 7 Member of the Yanchang Formation directly controls reservoir quality, and consequently influences shale oil productivity. The Ansai Oilfield is facing depleted conventional resource and difficult reserve replacement, making shale oil reservoirs the main target for reserve growth. Therefore, characterizing the pore structure and constraining the genesis of different reservoirs is of great significance for oilfield exploration and development.   Methods  Targeting the interbedded shale oil reservoirs in the Chang 7 Member of the Ansai Oilfield, we carried out experiments including scanning electron microscopy, casting thin sections, low-temperature nitrogen adsorption, high-pressure mercury intrusion, and nuclear magnetic resonance, to identify the influence of pore size on the quality of the reservoirs, and to reveal the genesis of different reservoirs from the perspectives of depositional environment and diagenesis.   Results  The reservoir pores are predominantly composed of feldspar pores, residual intergranular pores, intergranular pores, clay intergranular pores, and a small number of microcracks. The feldspar pores are mainly micrometer-sized, while clay intergranular pores are dominantly nanometer-sized. The reservoir exhibits relatively high discharge pressures and low mercury injection saturation, with pore-throat radii predominantly at the nanometer scale. Most pores with diameters below 500 μm are open-type parallel plate-shaped and slit-shaped, with a small number of ink-bottle-type pores also developed. The pore sizes in the reservoir are predominantly below 300 μm, and as physical properties improve, the proportion of larger pores gradually increases.  Conclusion  The genesis of high-quality reservoirs can be categorized into two types. In the northeast, closer to the provenance area, strong hydrodynamic conditions lead to better sorting of rock particles, facilitating the development of chlorite coatings within the reservoir. These chlorite coatings can protect primary intergranular pores between particles, allowing more residual intergranular pores to be preserved after compaction, thus forming high-quality reservoirs. In contrast, the southwest area, being farther from the provenance, exhibits increasing water depth and weaker hydrodynamics. Due to its proximity to the source rock development zone, the reservoir is more susceptible to dissolution of organic acids from hydrocarbon source rocks, leading to the formation of numerous dissolution pores and the development of high-quality reservoirs. [ Significance ] The study can support the efficient exploration and development of shale reservoirs in the region.